Penyusunan naskah pidato dan public speaking pada remaja RW. 03 Meruyung, Limo Depok binaan AM EDU center - Eko Yulianto; Bambang Sumadyo; Adi Permana (Lancar Media Komunikasi, 2022)
The purpose of this community service activity is to provide knowledge to RW Youth. 03 Meruyung Village, Limo District, Depok City Assisted by AM Edu Center about the importance of designing speech texts as a provision for public speaking. The abdimas partners were given socialization on how to design an effective speech text as a provision for social life in the future. The method used in this activity is the method of discussion and practice of compiling speech texts interspersed with screenings of films and videos that contain presentations of effective text drafting designs. The output produced in this activity is an article which will be given back to the participants. To measure changes in knowledge in this activity, a questionnaire was also distributed to the audience to measure knowledge before and after the socialization activity.